Turbo Pascal programmer's library - Jamsa, Kris A.; Nameroff, Steven (Osborne : McGraw-Hill Book Company, 1988)
Pascal was developed in 1971 by Niklaus Wirth in response to a growing need for a structured, modular, strongly typed, and systematic programming language.
1. Unique features of turbo pascal -- 2. Mathematical routines -- 3. Array manipulation -- 4. searching and sorting -- 5. String manipulation -- 6. Pointers and dynamic data structures -- 7. Input and output -- 8. Menus and special I/O -- 9. ROM-BIOS and DOS interface -- 10. File manipulation routines -- 11. Programming the pipe -- 12. Turbo pascal numerical methods toolbox -- 13. Graphics and the graphix toolbox -- 14. Turbo pascal numerical methods toolbox -- 15. Date and time manipulation routines -- 16. Miscellaneous routines.
Includes bibliographical references and index.
Keywords: PASCAL (COMPUTER PROGRAM LANGUAGE)